Temporal and spatial changes of phytoplankton in the coastal waters of Banias city - درويش, فيروز; المرعي, رهف (Latakia University Journal -Biological Sciences Series, 2021)
This research was carried out on the coastal waters of Banias city, as a complement to the previous studies along the Syrian coast. Five stations were selected based on their different environmental characteristics, and their continuous exposure to sources pollution (organic - thermal - oil). Nine sampling were carried out during the study period, which lasted from February 2019 until October 2019. Water samples were collected for analysis and determine the concentrations of chlorophyll (a) and determine the speciess of phytoplankton, which collected, in addition to field measurements of some physical and chemical factors (temperature - salinity). The registered concentrations are ranged between 0.1 - 5.3 mg /m3 for chlorophyll (a). Values ​​of the total abundance ranged between 1000 - 780*103 cell/L. This study has recorded 91 species of phytoplankton in study sites, distributed as follow: (61) species of Diatoms, (26) species of Dinoflagellates, (1) species of Silicoflagellates, (2) species of Chlorophyta, and 1 species of Cyanophyta.